Development of the welfare economy and the economy of impressions on the basis of inclusion and social innovation - Nataliia Kraus; Kateryna Kraus (Economic Forum, 2025)
The relevance of this study lies in the increasing number of countries worldwide that are prioritising population welfare as a key policy objective. In the post-war period, Ukraine should focus on fostering inclusiveness and cultivating an equitable culture that takes into account the interests of all members of society. This research aimed to examine the components of inclusive development within the national economy, based on social innovations, and to identify the relationship between the welfare economy and the experience economy. The primary outcomes of the study included the justification and exploration of the elements of inclusive economic development grounded in social innovations that seek to enhance the population's welfare. Particular attention was given to social innovations that promote the creation of a barrier-free environment within Ukrainian society. Data on the compound annual growth rate of the global segmented entertainment and media market for 2024-2028 were analysed, indicating the dynamic evolution of the experience economy. The author's perspective on the interrelationship between the welfare economy and the experience economy in the context of inclusive development was presented. An overview of existing concepts and approaches to the formation and advancement of the welfare economy was provided. The First and Second Welfare Theorems were examined, along with the foundational ideas introduced by the pioneering scholars of welfare theory. The practical value of the study lies in substantiating the influence of social innovations, digital technologies, inclusion, and accessibility on consumption patterns within both the welfare and experience economies.
Keywords: 330; experience economy; inclusive development; barrier-free; accessibility; virtual world; inequality